DETECTION OF SMALL NON-CODING RNA, RSAE, REGULATES THE ICA OPERON EXPRESSION IN STAPHYLOCOCCUS AUREUS IN HOLLY KARBALA CITY - Wannas, Zahraa Mohammed; Hassani, Hayfa H. (Eastern Ukrainian Medical Journal, 2025)
Introduction. One of the pathogenic mechanisms by which Staphylococcus aureus is able to adhere to and persist on many types of medical equipment is its ability to produce biofilms. S. aureus conserved small noncoding RNA, RsaE, is known to regulate several metabolic processes. Aim: This study aimed to investigate the correlation between small non-coding RNA RsaE and biofilm formation ica operon of S. aureus. Material and Methods. In this study, different clinical samples (n=250) were collected from patients who attended to the hospitals at Holly Karbala City, Iraq. Based on cultural and biochemical approaches, the bacteria isolated from clinical samples were identified as S. aureus (n=60), which was further confirmed by Vitek2 compact. To determine the potential of S. aureus for biofilm formation, a microtiter plate as a quantitative method was used. Thereafter, the biofilm genes icaADBC and regulatory gene small non-coding RNA, RsaE, were detected using a polymerase chain reaction. Finally, the expression of biofilm operon icaADBC and regulatory gene rsaE was estimated in S.aureus isolates using a real-time quantitative PCR method. Results. S. aureus (n=60) was isolated from different clinical samples (n=250) and identified according to the morphological and biochemical characteristics. Depending on the quantity of biofilm formation, the isolates were divided into strong (25%), moderate (67%), and weak (8.3%). All isolates (100%) had biofilm genes icaADBC, and regulatory small non-coding RNA gene, rsaE. Notable, S.aureus isolates with strong and moderate biofilm formation revealed high expression levels in icaA, icaD, and rsaE genes while S.aureus isolates with weak biofilm formation appeared with low expression levels of icaA, icaD, and rsaE genes. Conclusion. This study proved that rsaE was responsible for the regulation of biofilm formation in the S.aureus clinical isolates through positively controlling the biofilm genes icaADBC.